The link between regularity and strong-pi-regularity - Patrício, Pedro (2010)
It is shown that if all powers of a ring element $a$ are regular, then $a$ will be strongly-pi-regular exactly when a suitable word in the powers of $a$ and their inner inverses is a unit.